PKS dan Negara Syariah - Ida Rochmawati (Proceedings of Annual Conference for Muslim Scholars, 2018)
This paper will explore the political ideology of PKS in realizing the ideals and goals of the party in an evolutive way, how the implementation of PKS political ideology is done gradually and programmed to achieve a political success. With ideological approach this article try to explain the shift of PKS ideology from year to year slowly but surely has gained a position well established in the map of politics in Indonesia and long-term struggle in realizing the ideology of shariā implementation, although in its journey there are various frictions that erode the eshtablishment of ideology. This is inseparable from the implementation of ideology and movement strategy that was built carefully. From the tarbiyah movement that characterized the party then turned into a social movement and party that has militant cadres ranging from grassroot level to who are in a strategic position. PKS is born from the spirit of deep-rooted Islamism. Its existence is not due to the political influence of great figures that surround it, but born from the spirit of young people who aspire to the implementation of Islamic shariā in socio-political life in Indonesia. of course these ideals are not born just like that. There is a major influence of the Islamic world outside Indonesia that helped shape and formulate the ideas of Islamism